2010
DOI: 10.1073/pnas.1002971107
|View full text |Cite
|
Sign up to set email alerts
|

International population movements and regional Plasmodium falciparum malaria elimination strategies

Abstract: Calls for the eradication of malaria require the development of global and regional strategies based on a strong and consistent evidence base. Evidence from the previous global malaria eradication program and more recent transborder control campaigns have shown the importance of accounting for human movement in introducing infections to areas targeted for elimination. Here, census-based migration data were analyzed with network analysis tools, Plasmodium falciparum malaria transmission maps, and global populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
163
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(173 citation statements)
references
References 36 publications
7
163
1
1
Order By: Relevance
“…This information is important from the public health perspective, because local mosquito-borne transmission must be distinguished from real imported infections in malaria-receptive areas, such as southern Europe, [8][9][10][11][12] and endemic countries with malaria elimination programs (e.g., Zanzibar, Saudi Arabia, and Sri Lanka). [13][14][15][16] Limited sequence analyses of antigen-coding nuclear loci have revealed differences between local and imported parasites 17 as well as between parasite strains imported from different endemic regions. 18 However, the 6-kb mitochondrial genome of malaria parasites may have some advantages over currently available nuclear markers as a source of information on P. vivax polymorphisms for epidemiological studies for a few reasons.…”
Section: Introductionmentioning
confidence: 99%
“…This information is important from the public health perspective, because local mosquito-borne transmission must be distinguished from real imported infections in malaria-receptive areas, such as southern Europe, [8][9][10][11][12] and endemic countries with malaria elimination programs (e.g., Zanzibar, Saudi Arabia, and Sri Lanka). [13][14][15][16] Limited sequence analyses of antigen-coding nuclear loci have revealed differences between local and imported parasites 17 as well as between parasite strains imported from different endemic regions. 18 However, the 6-kb mitochondrial genome of malaria parasites may have some advantages over currently available nuclear markers as a source of information on P. vivax polymorphisms for epidemiological studies for a few reasons.…”
Section: Introductionmentioning
confidence: 99%
“…practices among affected communities in a study reported by Tatem et al (2010). The lower prevalence (34.29%) observed among participants with good knowledge about malaria prevention and treatment compared with those with poor knowledge (69.05%) is an indication that community's attitudes and beliefs regarding malaria treatment and treatment seeking behaviour had significant influence on the burden of disease induced by malaria as explained by Tatem et al (2010) and Olorunniyi and Morenikeji (2013). The wide acceptance (84.13%) of mosquito bites as the cause of malaria may be attributed to higher access to the media and availability and use of modern health facilities in the community.…”
Section: Hospital Visits In Egh Pre-and Post-irs Exercisementioning
confidence: 95%
“…Although the governance and management structures for most of the networks were large, led by individuals rather than institutions, and heavily dependent on donors, the objectives of these historical networks are still valid. The national groupings adopted by African surveillance networks have subsequently been vindicated by studies into malaria migration 74 and drug-resistance dispersal patterns (figure 3). 65 Results of both of these studies show the regional character of malaria populations and reflect the strong economic, political, and cultural linkages between countries.…”
Section: National and Regional Routine Sentinel Surveillance Networkmentioning
confidence: 99%